Relationship Between LBW and Stunting Incidence in Toddler on Terong Tawah Village, West Lombok - Diarna, Ni Putu Della; Jihad, Jihad; Efiantari, Lina; Wijaya, Devina Adelina; Budiyasa, I Komang Sutrisna (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Prevalence of stunting in West Nusa Tenggara (NTB) exceeded the Indonesian average in 2019 with the second highest cases found in West Lombok Regency. Stunting is caused by many factors, either history of Low Birth Weight (LBW). Research shows that babies with LBW have slower growth and development. This study aims to analyze the relationship between LBW and stunting incidence in children aged 0-60 months in Terong Tawah Village, Labuapi District, West Lombok Regency. The study used an observational analytical method with a retrospective case-control approach. Data analyzed with SPSS software, The results of the study showed a significant relationship between LBW and stunting incidence (p 0.043; OR = 4.750).